Yogurt fortified with vitamins and probiotics impacts the frequency of upper respiratory tract infections but not gut microbiome: A multicenter double-blind placebo controlled randomized study. (August 2021) - Odintsova, Vera; Klimenko, Natalia; Tyakht, Alexander; Volokh, Olesya; Popov, Vladimir; Alexeev, Dmitry; Berezhnaya, Yulia
Graphical abstract: Highlights: Vitamins and probiotics may contribute to normal immune function. A yogurt fortified with vitamins and probiotic Lacticaseibacillus was consumed during the intervention. There were positive effects on URTI related parameters. The gut microbiome dynamics were not different from ones of the control group. Abstract: Probiotics and vitamins can impact immune responses and modulate gut microbiome. We evaluated the effects of consuming a yogurt fortified with vitamins and probiotic Lacticaseibacillus casei and rhamnosus on upper respiratory tract infections frequency and gut microbiome during a 3-month intervention. The study included 2 case groups (consuming different flavours) and a placebo group of healthy adults (n = 158–160 in each group). The effects on URTI-related parameters in both case groups were gender-specific. The female subjects had lower URTI incidence and frequency, while for the males no significant differences were found. The URTI duration was shorter in one of the probiotic groups for females and in both such groups - for males. The observed changes in microbiome composition, blood and stool parameters were not different from those observed in the placebo group. Consumption of fortified fermented dairy foods is promising for improving immunity status within the general population.